(untitled) (El-Wahat Journal for Research and Studies, 2025)
the research deals with the study of legal requirements for applying the rental credit formula in the algerian banking system, where was a need to find economic alternatives that would make establishments and individuals more likely to engage in the consequences of debt and usury, the rental interest was one of the most important innovative new financing formulas by which economic dealers could obtain the required financing. Therefore, we aim to clarify the legal requirements that the algerian financial institutions should take into account when applying this alternative. Thus, we concluded that the rental credit contract is permissible if the legal controls are taken into account in it; such as transferring some obligations of the lessee to the lessor without abuse of the right of rescission, and applying to the contract the provisions of the lease for the duration of the lease and the provisions of sale when owning the property, then we decided to recommend the necessity of establishing of the sharia supervisory boards and activating in algerian conventional banks. Key words: Legitimate requirements, rental credit, capital assets, Lease credit, Rent ending in delay.